Rupture uterus: a prospective observational study of 25 consecutive cases in a tertiary referral centre in South India - Desai, Rashmi S; Kamat, Amitha V (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Uterine rupture in pregnancy is a rare though catastrophic complication with a high incidence of foetal and maternal morbidity. It appeared to be on the decline in recent times, prompting us to analyse the clinical picture now. The objective of the study was to study the risk factors, clinical profile and consequences of uterine rupture on maternal and perinatal outcome. Methods: A prospective observational study of 25 consecutive cases of uterine rupture was carried out between July 2013 and October 2015. All the cases of rupture uterus either referred or diagnosed after admission were included. Detailed demographic data, past and present obstetric events, time taken to reach the referral centre, the reasons for any delay, mode of presentation, type of rupture, management and maternal and foetal outcomes were analysed. Results: The incidence of rupture was 1 in 915 deliveries. Seventy-two per cent of them were referred cases. Average time to reach from referral centre was 4.3 hours, the common reasons for delay being patient factors (33%), transport problems (38%) and delayed referrals (22%). Previous caesarean section was the most common predisposing factor (56%). Sixty-four per cent of the ruptures were diagnosed clinically. Eighty-four per cent of the ruptures were complete. Sub-total hysterectomy was carried out in 14 (56%) patients. Internal iliac artery ligation (20%) and bladder repair (8%) were sometimes required. All women required blood transfusion. Perinatal mortality was seen in 76%. There was no maternal mortality. Conclusions: Uterine rupture is a cause of severe acute maternal morbidity and very high perinatal mortality. Delay in referral and diagnosis can lead to significant maternal morbidity and hysterectomy.